Psychophysical evaluation of control scheme designed for optimal kinesthetic perception in scaled teleoperation - Hyoung Il Son; Bhattacharjee, Tapomayukh; Hoeryong Jung; Doo Yong Lee (2010 IEEE International Conference on Robotics and Automation, 2010)
This paper focuses on psychophysical evaluation of the control scheme developed to optimize the kinesthetic perception during the scaled teleoperation. The control problem is formulated as a multi-objective constrained optimization. The objective function is a metric which quantifies the detection and discrimination capacity of the human operator. The constraints are position tracking accuracy and absolute stability of the scaled teleoperation. Two popular control architectures, i.e., the position-position and the force-position control architectures are considered in this paper. The method of limits is employed in this paper to conduct the psychophysical experiments and evaluation. Results show that the developed control scheme is more effective in increasing the detection and discrimination capacity of human subjects as compared to the traditional transparency-optimized control laws.